OCT4 silencing triggers its epigenetic repression and impairs the osteogenic and adipogenic differentiation of mesenchymal stromal cells - Malvicini, Ricardo (2019)
Mechanisms mediating mesenchymal stromal/stem cells’ (MSCs) multipotency are unclear. Although the expression of the pluripotency factor OCT4 has been detected in MSCs, whether it has a functional role in adult stem cells is still controversial. We hypothesized that a physiological expression level of OCT4 is important to regulate MSCs’ multipotency and trigger differentiation in response to environmental signals. Here, we specifically suppressed OCT4 in MSCs by using siRNA technology before directed differentiation. OCT4 expression levels were reduced by 82% in siOCT4-MSCs, compared with controls. Interestingly, siOCT4-MSCs also presented a hypermethylated OCT4 promoter. OCT4 silencing significantly impaired the ability of MSCs to differentiate into osteoblasts. Histologic and macroscopic analysis showed a lower degree of mineralization in siOCT4-MSCs than in controls. Moreover, OCT4 silencing prevented the up-regulation of osteoblast lineage-associated genes during differentiation. Similarly, OCT4 silencing resulted in decreased MSC differentiation potential towards the adipogenic lineage. The accumulation of lipids was reduced 3.0-fold in siOCT4-MSCs, compared with controls. The up-regulation of genes engaged in the early stages of adipogenesis was also suppressed in siOCT4-MSCs. Our findings provide evidence of a functional role for OCT4 in MSCs and indicate that a basal expression of this transcription factor is essential for their multipotent capacity.